VESICOURETERAL REFLUX, ETIOLOGY, DIAGNOSTICS, TREATMENT AND COMPLICATIONS-REVIEW ARTICLE - Bundovska, Smiljana; Selim, Gjulsen (Journal of Morphological Sciences; Vol 3 No 3 (2020): JMS, 2020)
Primary vesicoureteral reflux (VUR) is the commonest congenital urological abnormality in children, which is associated with an increased risk of urinary tract infection (UTI) and renal scarring, also called reflux nephropathy (RN), with a risk of late consequences: proteinuria, focal segmental glomerular sclerosis, hypertension, and chronic renal disease (CKD). Key words: vesicoureteral reflux, abnormality, children.